Update of the list of qualified presumption of safety (QPS) recommended microbiological agents intentionally added to food or feed as notified to EFSA 20: Suitability of taxonomic units notified to EFSA until March 2024 - EFSA Panel on Biological Hazards (BIOHAZ); Konstantinos Koutsoumanis; Ana Allende; Avelino Alvarez‐Ordóñez; Declan Bolton; Sara Bover‐Cid; Marianne Chemaly; Alessandra De Cesare; Friederike Hilbert; Roland Lindqvist; Maarten Nauta; Romolo Nonno; et al. (EFSA Journal, 2024)
Abstract The qualified presumption of safety (QPS) process was developed to provide a safety assessment approach for microorganisms intended for use in food or feed chains. In the period covered by this statement, no new information was found that would change the status of previously recommended QPS TUs. The TUs in the QPS list were updated based on a verification, against their respective authoritative databases, of the correctness of the names and completeness of synonyms. A new procedure has been established to ensure the TUs are kept up to date in relation to recent taxonomical insights. Of 81 microorganisms notified to EFSA between October 2023 and March 2024 (45 as feed additives, 25 as food enzymes or additives, 11 as novel foods), 75 were not evaluated because: 15 were filamentous fungi, 1 was Enterococcus faecium, 10 were Escherichia coli, 1 was a Streptomyces (all excluded from the QPS evaluation) and 46 were TUs that already have a QPS status. Two of the other eight notifications were already evaluated for a possible QPS status in the previous Panel Statement: Heyndrickxia faecalis (previously Weizmannia faecalis) and Serratia marcescens. One was notified at genus level so could not be assessed for QPS status. The other five notifications belonging to five TUs were assessed for possible QPS status. Akkermansia muciniphila and Actinomadura roseirufa were still not recommended for QPS status due to safety concerns. Rhizobium radiobacter can be recommended for QPS status with the qualification for production purposes. Microbacterium arborescens and Burkholderia stagnalis cannot be included in the QPS list due to a lack of body of knowledge for its use in the food and feed chain and for B. stagnalis also due to safety concerns. A. roseirufa and B. stagnalis have been excluded from further QPS assessment.